(untitled) (Revista Nacional de Odontología, 2017)
Introduction: Class ii malocclusion has the highest prevalence among dentoskeletal alterations worldwide. In Colombia its prevalence is 74 %. Currently, one of the reason for administering timely treatments is the rapid response of bone and neuromuscular structures the younger the organism. Aim: To identify changes in the craniofacial complex by means of lateral X-rays of 11 patients with Class ii Division 1 malocclusion, who underwent functional orthopedic treatment with Klammt’s Elastic Open Activator (keoa). Method: We selected a sample of 11 patients with Class ii Division 1 malocclusion between 8 and 12 years old, who underwent functional orthopedic treatment. The selected patients required a lateral x-ray before starting the treatment and once a year thereafter; the craniofacial complex changes of the patients undergoing treatment were analyzed. Results: In all 11 patients, Class ii Division 1 malocclusion was intercepted in a timely manner. A statistically significant decrease in anb, 1/Bap, 1 sup/1 inf, and overjet was perceived. Conclusion: In this study it was observed that keoa in the treatment of Class ii Division 1 malocclusion produced inhibited anterior growth of the upper dentoalveolar area, verticalization of upper incisors, restricted anterior migration of upper molars, and anterior positioning of point B.